Return on Assets (ROA), Leverage, And Firm Size on Tax Avoidance (Registered Banking Companies on IDX 2014-2018) - Oktaviani Sari; Siti Nurlaela; Kartika Titisari (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
The purpose of this study is to test and analyze the partial effect of return on assets, leverage, and firm size on tax avoidance, then test and analyze the effect of simultaneously return on assets, leverage, and firm size on tax avoidance. The design of this study is a quantitative study with a cross-sectional method. The data source uses secondary data in the form of financial statements of all banking companies listed on the IDIX for the period 2014-2018. Population and sampling using purposive sampling technique. The analysis technique uses multiple linear regression. The results showed that ROA partially had a significant and negatively related effect on tax avoidance, Leverage partially had no significant effect and negatively related to tax avoidance, firm size partially had no significant and negatively related effect on tax avoidance, and ROA, Leverage, and Firm Size simultaneously has a significant and positive relationship to tax avoidance.